The Basin of Mexico : critical environmental issues and sustainability - Ezcurra, Exequiel (UNU studies on critical environmental regions., 1999)
"The Basin of Mexico discusses the question of urban sustainability in Mexico City, one of the largest megacities on earth. Mexico City is an immense laboratory that reflects the environmental viability of the large cities of the developing world." "For some environmentalists, the urban and demographic growth of the Basin of Mexico is of grave concern, not only because of the attendant socio-economic consequences of such an immense concentration of population, but also because of the pressures that the clustering of some 18 million people may inflict on the environment. For others, the urban concentration of Mexico City is the logical result of the industrial development and the technological progress of the twentieth century, and does not represent a problem in itself, as technological development may provide the means to defeat the environmental and health problems spawned by urban growth." "The book examines some of these questions in a historic perspective, arguing that the depletion of natural resources in the Basin of Mexico is not just a recent phenomenon."--Jacket